Prevalence of hypertension and pre-hypertension among secondary school students - Qaddumi, Jamal; Holm, Margo; Alkhawaldeh, Abdullah; Albashtawy, Mohammed; AL Omari, Omar; Batiha, Abdul-Monim; Alhalaiqa, Fadwa; Suliman, Mohammad; Aljohani, Khalid; Da’she, Ayat (International Journal of Advanced Nursing Studies, 2016)
Hypertension and pre-hypertension are major contributors to morbidity. Early detection of hypertension and pre-hypertension among adolescents may prevent their complications. A cross-sectional study was conducted to estimate the prevalence of hypertension and pre-hypertension among adolescents attending government high schools in Nablus city, Palestine and to identify associated factors, in a sample of 487 adolescents aged 16-18 years in the year 2016. Associations between hypertension, pre-hypertension and known contributing factors were analyzed with Chi-square tests.The prevalence of hypertension and pre-hypertension were 59.2%. Body Mass Index (BMI) was significantly associated with a greater prevalence of hypertension (normal weight 13.1%, overweight 33.3%, and obesity 54.8 %) and pre-hypertension (normal weight 40.4%, overweight 47.4% and obesity 40.5%).The results confirmed a prevalence of hypertension and pre-hypertension among adolescents. Of known contributing factors studied, gender, age, BMI, and family history of hypertension were significantly associated with a greater prevalence of hypertension or pre-hypertension.